A new Liopeltis Fitzinger, 1843 (Squamata: Colubridae) from Pulau Tioman, Peninsular Malaysia - Som, Hannah E.; Grismer, L. Lee; Wood, Perry L. Jr.; Quah, Evan S. H.; Brown, Rafe M.; Diesmos, Arvin C.; Weinell, Jeffrey L.; Stuart, Bryan L. (Zootaxa, 2020)
Liopeltis is a genus of poorly known, infrequently sampled species of colubrid snakes in tropical Asia. We collected a specimen of Liopeltis from Pulau Tioman, Peninsular Malaysia, that superficially resembled L. philippina, a rare species that is endemic to the Palawan Pleistocene Aggregate Island Complex, western Philippines. We analyzed morphological and mitochondrial DNA sequence data from the Pulau Tioman specimen and found distinct differences to L. philippina and all other congeners. On the basis of these corroborated lines of evidence, the Pulau Tioman specimen is described as a new species, L. tiomanica sp. nov. The new species occurs in sympatry with L. tricolor on Pulau Tioman, and our description of L. tiomanica sp. nov. brings the number of endemic amphibians and reptiles on Pulau Tioman to 12.